Sesotho figurative language: Ineffective conversational strategy in commissions of enquiry. Issue 4 (2nd October 2022) - Mabena, Mampoi Irene; Sobane, Konosoang
Abstract: Commissions of enquiry have become a common platform for establishing facts where there have been disputes. They are often established to unpack the facts that would have led to controversies and make recommendations for solutions to such conflicts. Language then becomes an essential tool that facilitates extracting information that helps the commission to get to the truth and make informed recommendations. This article critically analyses the role played by Sesotho figurative language in the Leon and Phumaphi commissions of enquiry in Lesotho. This is a non-intrusive study that relied on audio recordings that were made during the enquiries. The article argues that figurative language was a conversationally ineffective communicative strategy that withheld information from the commissioners who were not speakers of Sesotho, the home language for the majority of participants who testified before the commissions. In the end, the implications of the study for transforming conversational events in commissions of enquiry are discussed.